Penerapan Metode Ward & Peppard dalam Analisis Strategi SI/TI di PT Imused Satria Muda - Tiya Utriani; Futikhat Salsabila; Indri Wahyuningsih; Banu Dwi Putranto; Ito Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The rapid advancement of information technology has compelled digital marketing companies to enhance efficiency and system integration to improve business performance. PT Imused Satria Muda, a digital marketing company focusing on beauty and herbal product promotion, faces challenges in integrating its information systems across divisions such as advertising, content creation, and customer service. This study aims to formulate an information systems and information technology (IS/IT) strategy aligned with the company’s business strategy using the Ward and Peppard methodology. A descriptive qualitative approach was employed, with data collected through observation, documentation review, and structured interviews. The analysis utilized SWOT, Value Chain, and McFarlan Strategic Grid tools to identify the internal and external conditions of the business and IS/IT environments. The results indicate that PT Imused Satria Muda requires the development of a cloud-based Customer Relationship Management (CRM) system, a Digital Campaign Dashboard, and marketing automation tools to enhance digital campaign effectiveness. The implementation plan is divided into short- and long-term stages over five years, focusing on data integration, information security, and IT human resource competency improvement. The proposed strategy is expected to increase operational efficiency and strengthen the company’s competitiveness within the dynamic digital marketing industry.